Quality of Life among Children with Osteogenesis Imperfecta Receiving Bisphosphonate Therapy Before and during the 1st Year of the COVID-19 Pandemic in Dr. Soetomo Hospital, Surabaya - Mustikasari, Rahma Ira; Rochmah, Nur; Faizi, Muhammad; Irwanto, Irwanto (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Osteogenesis imperfecta (OI) is a chronic illness caused by a connective tissue disorder that may lead to frequent fractures. Therefore, it may influence the quality of life (QoL). The study on QoL among children with OI during the coronavirus disease-19 (COVID-19) pandemic is still limited. AIM: This study aims to evaluate QoL before and during the COVID-19 pandemic in children with OI. METHODS: This cross-sectional study took place in the Pediatric Endocrinology Outpatient Clinic at Dr. Soetomo General Hospital, Surabaya, in 2020. The pre-pandemic data came from 2019 medical records. The questionnaire used was the Pediatric Quality of Life Inventory (PedsQL) 4.0 generic core. Twenty-two patients joined the study; 11/22 of them were girls. RESULTS: The mean age, fracture, and frequency of zoledronic acid treatment were 6.9 years old, 2.5×/year, and 7.1×/year, respectively. The PedsQL comparisons before and during the first year of the COVID-19 pandemic in each dimension were: Physical (49.57 vs. 42.76; p = 0.001), emotional (63.41 vs. 54.54; p = 0.001), social (58.86 vs. 53.86; p = 0.015), and school functioning (66.13 vs. 56.74; p = 0.001), respectively. The most affected dimension was school functioning (mean difference (minimum–maximum): (−9.39) (−14.28–[−4.49]), whereas the physical, emotional, and social functioning were 6.81 (3.43–10.19), 8.86 (5.06–12.67), and −5.00 (−8.93–(−1.07)), respectively. CONCLUSION: The QoL in children with OI during the COVID-19 pandemic was worst, especially in the school functioning dimension. Online consultation options may be beneficial to improving the QoL.